2021
DOI: 10.1186/s12889-021-10443-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health surveillance system attributes: the case of neglected tropical diseases in Kenya

Abstract: Background Control of preventive chemotherapy-targeted neglected tropical diseases (PC-NTDs) relies on strengthened health systems. Efficient health information systems provide an impetus to achieving the sustainable development goal aimed at ending PC-NTD epidemics. However, there is limited assessment of surveillance system functions linked to PC-NTDs and hinged on optimum performance of surveillance system attributes. The study aimed to evaluate surveillance system attributes based on health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Phase II: Primary data surveys on surveillance core, support and attribute functions concerning PC-NTDs [28,29] The first phase described surveillance system assessment studies previously conducted in the African region, which identified broad recommendations to improve the existing surveillance systems; however, these recommendations were inclined to notifiable diseases considered of national priority in African countries. Therefore, based on the premise that diseases targeted for control or elimination were to be accorded priority commensurate to notifiable diseases, the second phase entailed conducting health worker surveys involving primary data collection to assess performance of surveillance core, support and attribute functions concerning PC-NTDs endemic in Kenya.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phase II: Primary data surveys on surveillance core, support and attribute functions concerning PC-NTDs [28,29] The first phase described surveillance system assessment studies previously conducted in the African region, which identified broad recommendations to improve the existing surveillance systems; however, these recommendations were inclined to notifiable diseases considered of national priority in African countries. Therefore, based on the premise that diseases targeted for control or elimination were to be accorded priority commensurate to notifiable diseases, the second phase entailed conducting health worker surveys involving primary data collection to assess performance of surveillance core, support and attribute functions concerning PC-NTDs endemic in Kenya.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the main recommendations based on a high degree of groundedness encompassed provision of surveillance guidelines for supervision, properly constituted supervisory teams, regular supervision from higher levels, frequent provision of PC-NTDs updates, regular sensitisation and involvement of all health workers in surveillance activities, enhanced training on PC-NTDs surveillance, improved human resource capacity, provision of surveillance reporting and analysis tools, availing equipment and training materials, provision of adequate funding to facilitate surveillance activities and provision of reliable transportation. [29] The subsequent study aimed to evaluate surveillance system attributes based on health workers' perceptions concerning PC-NTDs endemic in Kenya. Health workers perceived the surveillance system to be simple (55%), acceptable (50%), stable (41%), flexible (41%), useful (51%) and to provide quality surveillance data (25%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations